(untitled) (Italian Journal of Public Health, 2007)
Background: Health impact assessment (HIA) prospectively judges the potential health impacts of pending decisions and feeds the assessment back into the decision making process. HIA is considered as a key tool for intersectoral collaboration. This article presents selected results of a mapping exercise on HIA in Europe. The mapping exercise is complemented by the presentation of a conceptual framework on the effectiveness of HIA and illustrative examples. Method: Two methodologies are employed in this article: First, the use of HIA across Europe is based on a survey conducted by 21 teams in 19 countries. A semi standardized questionnaire was employed, using a wide variety of sources. Second, for the discussion on the effectiveness of HIA, a conceptual framework using four types of effectiveness was employed. Results: HIA is a common practice only in a handful of European countries. In most of Europe, HIA is at an early developmental stage. The mapping exercise, however, provides evidence that HIA can work across all sectors and at all political level, although there is currently a focus on the local level. HIA is conducted in different countries by different sets of actors and organizations, reflecting the existing setup. The evidence on the effectiveness of HIA is still inconclusive. However, single case studies and upcoming evidence suggests that HIA has the capacity to inform and influence the decision making process. Conclusions: HIA can work and deliver. The variations in context across European countries have resulted in different forms of implementation and different dynamics of developing HIA.